Direct shear experiments on Solnhofen limestone at high temperature – an experimental analogue of transpression - Llana-Fúnez, S.; Rutter, E. H. (TRABAJOS DE GEOLOGÍA, 2009)
Specimens of Solnhofen limestone deformed dry in direct shear at 600 ºC, 200 MPa and bulk strain rates of ~5×10-3 s-1, show strain distributed heterogeneously with two high-strain bands close to the specimen edges accommodating most of the displacement. Strain analysis using calcite shape fabric and CPO (measured by EBSD) reveals that non-coaxial strain concentrating at the edges propagates towards the middle of the specimen, where flattening strain is predominant. Strain-hardening associated with flattening prevents initially non-coaxial strain from developing in the centre. Direct shear testing proves to be a good analogue for transpression when free boundaries are present to allow lateral extrusion.